UTILIZAÇÃO DA ULTRASSONOGRAFIA À BEIRA LEITO PARA AVALIAÇÃO DO CONTEÚDO GÁSTRICO: REVISÃO DA LITERATURA - Fernandes Guimaraes, Rodrigo; Felipe Maciel de Oliveira Brunet; Guilherme Brito de Souza; Juliana Ferreira Dias Xavier; Raphael Klênio Confessor de Sousa; Wallace Andrino da Silva (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2022)
Introduction: Perioperative aspiration of gastric contents is a serious complication of anesthesia and is associated with high morbimortality, which can result in severe pneumonia that requires mechanical ventilation support in up to one third of patients. With the advent of portable ultrasound, performing ultrasound at the service location has become relatively easy and feasible. Objective: To carry out a review of the literature seeking to evaluate clinical trials that assessed the determination of gastric volume and content by point-of-care ultrasound (POCUS). Method: The selection of works was carried out in August 2021 in the PUBMED database. Two search strategies were used: 1 - Ultrasound AND gastric AND fasting and anesthesia; and 2 - bedside AND ultrasound AND gastric. No time cut was performed. However, only clinical studies were considered in the present review. Results: The search ended with 10 articles that adequately met the inclusion criteria. Conclusion: The POCUS is a non-invasive technique that is very useful in determining gastric content and volume with high sensitivity and specificity, even if gastric content is uncertain. In addition, the application of POCUS to determine gastric emptying would present good sensitivity and specificity in discriminating patients with and without ileum. Keywords: Anesthesiology; Gastroenterology; Gastric emptying; Ultrasonography.